Editors between Support and Control by the Digital Infrastructure — Tracing the Peer Review Process with Data from an Editorial Management System - Hartstein, Judith; Blümel, Clemens (Frontiers in Research Metrics and Analytics, 2021)
Many journals now rely on editorial management systems, which are supposed to support the administration and decision making of editors, while aiming at making the process of communication faster and more transparent to both reviewers and authors. Yet, little is known about how these infrastructures, support, stabilize, transform or change existing editorial practices. Research suggests that editorial management systems as digital infrastructures are adapted to the local needs at scholarly journals and reflect main realms of activities. Recently, it has been established that in a minimal case, the peer review process is comprised of postulation, consultation, decision and administration. By exploring process generated data from a publisher’s editorial management system, we investigate the ways by which the digital infrastructure is used and how it represents the different realms of the process of peer review. How does the infrastructure support, strengthen or restrain editorial agency for administrating the process? In our study, we investigate editorial processes and practices with their data traces captured by an editorial management system. We do so by making use of the internal representation of manuscript life cycles from submission to decision for 14,000 manuscripts submitted to a biomedical publisher. Reconstructing the processes applying social network analysis, we found that the individual steps in the process have no strict order, other than could be expected with regard to the software patent. However, patterns can be observed, as to which stages manuscripts are most likely to go through in an ordered fashion. We also found the different realms of the peer review process represented in the system, some events, however, indicate that the infrastructure offers more control and observation of the peer review process, thereby strengthening the editorial role in the governance of peer review while at the same time the infrastructure oversees the editors’ performance.